1996
DOI: 10.1148/radiology.199.1.8633143
|View full text |Cite
|
Sign up to set email alerts
|

Phase II clinical evaluation of Gd-EOB-DTPA: dose, safety aspects, and pulse sequence.

Abstract: Gd-EOB-DTPA is an efficient, diagnostically useful, and safe contrast agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
180
2
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(193 citation statements)
references
References 0 publications
6
180
2
5
Order By: Relevance
“…Previous studies have demonstrated that Gd-EOB-DTPA is well tolerated and has no substantial adverse events and minor adverse events of 5.9% (6,7,19). In fact, there were no severe adverse effects in our study population.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies have demonstrated that Gd-EOB-DTPA is well tolerated and has no substantial adverse events and minor adverse events of 5.9% (6,7,19). In fact, there were no severe adverse effects in our study population.…”
Section: Discussionsupporting
confidence: 49%
“…17 A recent intraindividual comparison of 0.025 and 0.05 mmol/kg in patients with cirrhosis suggested significant improvement of liver-to-lesion (hepatocellular carcinoma) contrast in patients with decreased hepatic function (Child-Pugh class B disease) but not in patients with preserved hepatic function (Child-Pugh class A disease). 21 A study performed in the early stages of gadoxetic acid development also showed that liver-to-lesion contrast during the hepatobiliary phase was not necessarily higher using 0.05 compared with 0.025 mmol/kg, although the degree of enhancement compared to precontrast images was consistently higher using 0.05 mmol/kg.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The approved package insert dose of gadoxetic acid, 0.025 mmol/kg, yields a quarter of the dose of gadolinium of traditional formulation agents, including gadopentetate dimeglumine, gadoteridol, gadodiamide, gadoversetamide, and gadobenate dimeglumine. 15 This dose was determined based on preclinical studies 16,17 that demonstrated comparable early enhancement of hypervascular tumors between MRI with a 0.025 mmol/kg dose showed comparable early enhancement of hypervascular tumors to gadopentetate dimeglumine 16 A dose of 0.025 mmol/kg was also found to be the minimum effective dose during the hepatobiliary phase for the detection and characterization of lesions. 17 However, the imaging sequences used in these studies (both published in 1996) are no longer routinely used in clinical MR imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A bolus injection of gadoxetic acid provides a dual mode of action that allows imaging in the early dynamic phase (as with standard gadolinium chelates) and in the delayed phase (hepatobiliary phase) that is obtained 10 to 20 min after injection and lasts until 90 min after injection (7,8). In the hepatobiliary phase, malignant hepatic lesions lacking normally functioning hepatocytes are imaged as a defect of hepatocyte-selective enhancement as compared to the normal parenchyma (9).…”
mentioning
confidence: 99%